Use of Tiktok in Digital Business Marketing as a Promotional Media - Sundari; Ghaefira Nur Fatimah (Journal of Managiere and Business, 2024)
Every day we see children using today's information technology, known as social networking or media, due to its rapid development. There are even terms that refer to this technology, especially in our country. This technology is available in the form of software such as Facebook, Twitter, WhatsApp, TikTok, the Internet, and telephone, as well as hardware such as laptops and telephones. Now, Tik Tok users are getting creative and telling others about what they're up to. Through showing films, pictures, and songs, these devices facilitate information, can be transmitted, and explain stimulation for those who see, imitate, or disseminate it. If companies use social networks, especially TikTok, to promote their products, Indonesians, especially the Bengkulu community, have a promising market share. This study aims to learn how rnf.creation uses the Tik Tok social network to market its digital products. This research uses the observation method; Qualitative observation, using a descriptive approach, was used, and the file collection method was through question and answer and file storage. After the data is collected through question and answer, the file analysis method is used. In addition, the All relationships were analyzed to obtain initial presumptions and reach conclusions. The results show that rnf.creation has utilized social media to market its business on Instagram, which has gradually become better known and has many followers. Apart from that, they have used Digital Business to market their products, which allows social media users to see products posted on their Instagram accounts as well as using TikTok accounts as promotional media to attract customers on social media.